An effective optimization strategy and analysis for BaTiO3–Na0.5Bi0.5TiO3 system with colossal permittivity. Issue 9 (15th June 2017) - Li, Lingxia; Cai, Zhaoyang; Zhang, Ning; Li, Jiangteng
Abstract: Colossal permittivity (CP, ε＞10 4 ) behavior in BaTiO3 –Na0.5 Bi0.5 TiO3 (BT-NBT) ceramics has been studied, which showed extremely high permittivity up to 10 5 . Dielectric properties of samples showed Debye-like relaxations in the frequency range 20 Hz–30 MHz. Two different polarizations located in grain boundaries and grains respectively are responsible for the CP behavior and the models of defect charge compensation achieved by niobium doping are proposed to explain the phenomenon of abnormal variation of dielectric constant. By using defect engineering, a Nb-doped BaTiO3 ceramics with stable colossal permittivity (εr =1.3×10 4 at 1 kHz and room temperature)，high bulk resistivity (>10 10 Ω·cm) as well as relative low dielectric loss (tanδ 0.06) has been obtained over a wide temperature range of −55–150 °C, satisfying IEA X8R specification, which has a potential application prospect in high capacity solid supercapacitor.